Pusat Rehabilitasi Penderita Ketergantungan Napza Di Pekanbaru Dengan Pendekatan Healing Environment - Santoso, Nugroho Budi; Hidayat, Wahyu; Faisal, Gun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Narcotics misuse and circulation is one of the biggest problems in the country, especially in Riau province. However, the high number of narcotic violations is not balanced with the means and rehabilitation facilities that meet the standards. The available rehabilitation containers are still limited in terms and facilities. Therefore, this study aims to design a rehabilitation center for the most complete drug sufferers of NAPZA, so that it is the main reference for the rehabilitation service in Riau province and is a sample material for the place Existing rehabilitation. The method used in design is the Healing Environment approach by applying principles related to nature as the basis of healing. This is because nature can calm the mind and can affect the psychological and physical condition of rehabilitation patients so that it can help accelerate the healing process. The concept used is the concept of rehabilitation transformation, expected by this concept can unite between architecture and human health. The end result is a design of the NAPZA Addiction Rehabilitation Center which is able to provide rehabilitation activities.Keyword: Healing Environment, Pekanbaru, NAPZA, Rehabilitation Center